The Influence of Price Perception, Brand Image, and Consumer Satisfaction Towards Interest in Rebuying Zara Clothing Products in Jakarta - Firyal Nadhifah Fairuz; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
The purpose of this study is to see and analyze the Influence of Perceived Price, Brand Image, and Consumer Satisfaction on Repurchasing Interest for Zara clothing products in the city of Jakarta. This type of research uses descriptive quantitative methods and inferential analysis using primary data. The sample was determined by purposive sampling method with a total of 100 respondents. Data collection was carried out by providing a list of questions to respondents, namely consumers of Zara clothing products in the city of Jakarta, the questions given were about price perception, brand image, and consumer satisfaction, on repurchase intention. This research uses multiple linear regression analysis. The results showed that perceived price, brand image and consumer satisfaction had a positive and significant effect on the intention to repurchase Zara clothing products in the city of Jakarta.